PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN QUIZIZZ TERHADAP HASIL BELAJAR SISWA MATERI EKOSISTEM KELAS X DI SMA NEGERI 6 BALIKPAPAN - Samosir, Gaby Helena Tesalonika; Rambitan, Vandalita Maria Mahdalena; Herliani, Herliani; Lumowa, Sonja Tinneke (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Interview observations were carried out at SMA Negeri 6 Balikpapan and it was discovered that the learning model used still used the conventional model. This is the reason for carrying out this research which aims to find out how student learning outcomes are influenced by the problem-based learning (PBL) model which is assisted by the quizizz application. This study was conducted at SMA Negeri 6 Balikpapan, East Kalimantan, for one month, from April 22 to May 16 2024. The research sample included 32 students, one from each class, because a purposive sampling technique was used. Interviews, observations, tests, and documentation are data collection methods. The research results show that the t table value (2,576) exceeds the calculated t value (1,671) with a significance level of 0.05. The application of the Problem-Based learning model assisted by Quizzizz was able to improve the learning outcomes of Biology students in Class X of SMA Negeri 6 Balikpapan.